PENGARUH KECERDASAN EMOSIONAL, PERILAKU BELAJAR DAN MINAT BELAJAR TERHADAP TINGKAT PEMAHAMAN AKUNTANSI (Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Jurusan Akuntansi Universitas Islam Malang) - Lindy Aulia Nuryatni; Nur Diana; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The sample in this study used accounting study program students class 2017 and 2018, Faculty of Economics and Business, Islamic University of Malang. The data collection method used is by distributing online questionnaires from Google, a sample of 89 students. The sampling technique was purposive sampling. The method used in this research is quantitative research methods using multiple linear analysis techniques. And based on the partial test results, the variable Emotional Intelligence, Learning Behavior and Learning Interest have a positive and significant effect on the Level of Accounting Comprehension.Keywords : emotional intelligence, learning behavior, interest in learning, level of understanding of accounting